High Voltage Coil Current Sensor for DC-DC Converters Employing DDCC - M. Drinovsky; J. Hospodka (Radioengineering, 2015)
Current sensor is an integral part of every switching converter. It is used for over-current protection, regulation and in case of multiphase converters for balancing. A new high voltage current sensor for coil-based current sensing in DC-DC converters is presented. The sensor employs DDCC with high voltage input stage and gain trimming. The circuit has been simulated and implemented in 0.35 um BCD technology as part of a multiphase DC-DC converter where its function has been verified. The circuit is able to sustain common mode voltage on the input up to 40 V, it occupies 0.387*0.345 mm2 and consumes 3.2 mW typically.